Kepemimpinan dalam Rumah Tangga Perspektif Tafsir dan Analisis Gender - Nor Salam Salam (Qisth : Jurnal Studi dan Penelitian Hukum Islam, 2024)
This study examines the aspect of leadership in the family as stated in Surah al-Nisa verse 34 which states that men are leaders for women because Allah has given advantages to a man. Through the study of interpretation and gender analysis, this study concludes that leadership in the family is not taken for granted, or in terms of gender is not a natural gender, but rather the result of social construction. Therefore, leadership cannot be standardized on a particular gender, but is based on the aspect of capability possessed by both men and women.